2008
DOI: 10.1248/cpb.56.1502
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium Catalyzed 1,4-Conjugate Addition of 1,5-Azastibocines with Electron Deficient Olefins

Abstract: The rhodium-catalyzed reaction of Sb-aryl-1,5-azastibocines with a a,b b-unsaturated ketones and esters is described. Exclusive formation of 1,4-conjugate adduct was achieved in aqueous NMP (N-methyl-2-pyrrolidinone) in the presence of 5 mol% of [RhCl(cod)] 2 , and no formation of Heck adduct was observed in this condition. Reactions with various enones and enoates were also demonstrated to prove generality of the 1,4-conjugate addition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…From these results, it was concluded that 1,5-azastibocines 428 were good aryl donors in the 1,4-conjugate addition (Scheme 204). 353 The proposed catalytic cycle for the conjugate addition is similar to the mechanism for the 1,4-addition of organoboronic acid to enones (Scheme 205). 60 1,5-azastibocine was transmetallated to a suitable Rh catalyst to provide aryl-rhodium complex 430.…”
Section: Miscellaneousmentioning
confidence: 91%
See 2 more Smart Citations
“…From these results, it was concluded that 1,5-azastibocines 428 were good aryl donors in the 1,4-conjugate addition (Scheme 204). 353 The proposed catalytic cycle for the conjugate addition is similar to the mechanism for the 1,4-addition of organoboronic acid to enones (Scheme 205). 60 1,5-azastibocine was transmetallated to a suitable Rh catalyst to provide aryl-rhodium complex 430.…”
Section: Miscellaneousmentioning
confidence: 91%
“…350 It is noteworthy that alkyl zirconocene chloride is an ineffective reagent under the present reaction conditions, and the same was noticed in Rh(I)-catalyzed reactions with imines. [352][353][354][355] Since the transfer of the alkyl group from Zr to Rh is slower than the alkenyl group, 356 this 1,4-addition reaction of 1 is expected to involve the creation of alkenyl rhodium species via the transmetallation at the first stage. The overall process is illustrated in Scheme 195, in which the 1,4-adducts are obtained from a catalytic cycle as a Zr-enolate 403.…”
Section: Organozirconiumsmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27) We also reported that Sb(V) compounds work as useful pseudo-halides in Pd-catalyzed cross-coupling reactions.…”
mentioning
confidence: 98%
“…14,[23][24][25] In the course of our studies on organoantimony (Sb) compounds as synthetic reagents, we have recently demonstrated that Sb(III) compounds were efficient transmetallating agents for transition metal-catalyzed cross-coupling reactions. 26,27) We also reported that Sb(V) compounds work as useful pseudo-halides in Pd-catalyzed cross-coupling reactions. 28) These results stimulated us to employ them in Cu-mediated arylation of amines.…”
mentioning
confidence: 98%